Chirality Effects in Peptide Assembly Structures - Zheng, Yongfang; Mao, Kejing; Chen, Shixian; Zhu, Hu (Frontiers in Bioengineering and Biotechnology, 2021)
Peptide assembly structures have been widely exploited in fabricating biomaterials that are promising for medical applications. Peptides can self-organize into various highly ordered supramolecular architectures, such as nanofibril, nanobelt, nanotube, nanowire and vesicle. Detailed studies of the molecular mechanism by which this versatile building block is assembled can guide the design of peptide architectures with desired structure and functionality. It has been revealed that peptide assembly structures are highly sequence-dependent and sensitive to amino acid composition, the chirality of peptide and amino acid residues, and external factors, such as solvent, pH, and temperature. This mini-review focuses on the regulatory effects of chirality alteration on the structure and bioactivity of linear and cyclic peptide assemblies. In addition, chiral self-sorting and co-assembly of racemic peptide mixtures are discussed.